2022
DOI: 10.48550/arxiv.2206.03271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Effectiveness of Fine-tuning Versus Meta-reinforcement Learning

Abstract: Intelligent agents should have the ability to leverage knowledge from previously learned tasks in order to learn new ones quickly and efficiently. Meta-learning approaches have emerged as a popular solution to achieve this. However, metareinforcement learning (meta-RL) algorithms have thus far been restricted to simple environments with narrow task distributions. Moreover, the paradigm of pretraining followed by fine-tuning to adapt to new tasks has emerged as a simple yet effective solution in supervised and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…As explained at the beginning of the paper, previous work has shown that using hardware data to fine-tune a policy that has been pre-trained in simulation is a powerful approach to tackle the sim-2-real gap problem (e.g. [12,13,14,15]). These methods typically take the RL agent trained in simulation and continue its learning process using hardware data.…”
Section: D1 Cartpole Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As explained at the beginning of the paper, previous work has shown that using hardware data to fine-tune a policy that has been pre-trained in simulation is a powerful approach to tackle the sim-2-real gap problem (e.g. [12,13,14,15]). These methods typically take the RL agent trained in simulation and continue its learning process using hardware data.…”
Section: D1 Cartpole Resultsmentioning
confidence: 99%
“…Compared to these works, our primary contribution is to demonstrate how CLFs can be combined with model-free algorithms to rapidly learn stabilizing controllers for robotic systems. Fine-tuning with Real World Data: Recently, there has been much interest in using RL to finetune policies which have been pre-trained in simulation [12,13,14,15]. These methods typically optimize the same cost function with a large discount factor in both simulation and on the real robot.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The hope is that this representation holds meaningful structure for what's important for all tasks, thus letting the robot reuse the representation to efficiently learn new but related tasks. This has been shown to be more stable and scalable than metalearning [111], but still needs curating a large set of training tasks to robustly cover the test distribution.…”
Section: Feature Embeddingsmentioning
confidence: 99%
“…However, current meta-reinforcement learning algorithms are limited to simple environments with narrow task distributions [93][94][95][96] . A recent study showed that multi-task pre-training with fine-tuning on new tasks performs as well as or better than meta-pre-training with meta test-time adaptation [97] . Research considering large-scale pre-trained models in quadrupedal locomotion research is still in its infancy and needs further exploration.…”
Section: Large-scale Pre-training Of Drl Modelsmentioning
confidence: 99%